Reduction of Technetium(VII) by Desulfovibrio fructosovorans Is Mediated by the Nickel-Iron Hydrogenase - De Luca, Gilles (American Society for Microbiology, 2001)
Resting cells of the sulfate-reducing bacterium Desulfovibrio fructosovorans grown in the absence of sulfate had a very high Tc(VII)-reducing activity, which led to the formation of an insoluble black precipitate. The involvement of a periplasmic hydrogenase in Tc(VII) reduction was indicated (i) by the requirement for hydrogen as an electron donor, (ii) by the tolerance of this activity to oxygen, and (iii) by the inhibition of this activity by Cu(II). Moreover, a mutant carrying a deletion in the nickel-iron hydrogenase operon showed a dramatic decrease in the rate of Tc(VII) reduction. The restoration of Tc(VII) reduction by complementation of this mutation with nickel-iron hydrogenase genes demonstrated the specific involvement of the periplasmic nickel-iron hydrogenase in the mechanism in vivo. The Tc(VII)-reducing activity was also observed with cell extracts in the presence of hydrogen. Under these conditions, Tc(VII) was reduced enzymatically to soluble Tc(V) or precipitated to an insoluble black precipitate, depending on the chemical nature of the buffer used. The purified nickel-iron hydrogenase performed Tc(VII) reduction and precipitation at high rates. These series of genetic and biochemical approaches demonstrated that the periplasmic nickel-iron hydrogenase of sulfate-reducing bacteria functions as a Tc(VII) reductase. The role of cytochrome c(3) in the mechanism is also discussed.